Carboplatin, nab-paclitaxel plus atezolizumab in IMpower 130 trial: new weapons beyond controversies - De Giglio, Andrea; Nuvola, Giacomo; Dall’Olio, Filippo Gustavo (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
In the last decade, the management of advanced non-small cell lung cancer (NSCLC) has radically changed. The standard chemotherapy treatment based on histology constituted for 25 years the cornerstone of anticancer treatment, but was finally put aside when molecular diagnosis and precision medicine have modified the therapeutic algorithm.